Key factors of food waste worldwide and their impact on global food security - Ochilova Maftuna, (THE INNOVATION ECONOMY, 2026)
This article examines the global issue of food waste, highlighting its relevance, root causes, and socio-economic and environmental consequences. Based on official data from FAO and other international organizations, the paper discusses the amount of food wasted annually, associated economic losses, and the misuse of vital resources. The analysis systematically outlines the factors contributing to food waste across the production, storage, distribution, retail, and consumption stages. Special attention is given to consumer behavior, mismatches in marketing policies, and infrastructural deficiencies. The author emphasizes the role of digital technologies, information and communication tools, and educational programs in reducing food waste. In conclusion, the article argues for a comprehensive and efficient approach to ensuring global food security through waste prevention.